Race pattern of Men`s 110-M hurdles: Time analysis of Olympic hurdle performance - Tsiokanos, A.; Tsapoulos, D.; Giavroglou, A.; Tsarouchas, E. (Biology of Exercise, 2018)
In men`s 110-m hurdles event, technical parameters called direct performance descriptors are used for planning the distribution of an athlete`s efforts over the race. The purpose of the present study was to investigate the race behaviour of elite men sprint hurdlers, on the basis of selected time parameters, and the examination of the existence of a common race pattern in high level hurdle performance. The time data of the race performance between two consecutive Olympic Games were compared. The analysing subjects consisted of all men 110-m hurdle finalists in Athens 2004 and in Beijing 2008. No significant differences were revealed between the two competitions concerning to the means of approach run time (2.38 vs 2.42 s), run-in time (1.39 vs 1.40 s), intermediate touchdown times, interval times for the hurdle units and the corresponding average velocities (greatest units` velocities: 9.07 vs 9.02 m/s). Significant relationship exists between the intermediate times and final performance (r = 0.81 - 0.99). The time contribution of the first half of the race to the formation of the final performance is equal to the second one (50.1 - 50.4 % vs 49.9 - 49.6 %) and, generally, the standardised time parameters show the existence of a common race pattern in high level hurdle performance (the duration of the hurdle units, as a whole, constituted the 70.3 % and 70.0 % of the total race time in Athens 2004 and Beijing 2008 respectively). The presented biomechanical data provide coaches and athletes valuable information about hurdle technique for effective interventions in the training process.